2020
DOI: 10.1111/sms.13617
|View full text |Cite
|
Sign up to set email alerts
|

The bright and dark sides of motivation as predictors of enjoyment, intention, and exercise persistence

Abstract: Objective The present study aimed to examine the bright and dark sides of motivation, based on self‐determination theory, as predictors of enjoyment, intention to continue exercising, and exercise persistence. In addition, we analyzed the mediation role of each variable and tested the model invariance between male and female exercisers. Methods A total of 575 gym exercisers (female = 230) aged between 18 and 65 years (M = 34.07; SD = 11.47) participated in this study. All participants had at least 6 months of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
135
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(167 citation statements)
references
References 52 publications
(123 reference statements)
8
135
2
5
Order By: Relevance
“…The possible differences between physiological and psychological preparedness to increase training workload reinforce the importance of qualitative or quantitative psychological assessment throughout training, and further studies are needed to elucidate these aspects. In addition, it should be noted that SIT-WB participants had a certain level of autonomy over their training intensity, which may have also been important in satisfying basic psychological needs promoting autonomous motivation and enjoyment (Rodrigues et al, 2020). Improved fitness through training may also have served to build up competence and help maintain enjoyment over time (Heisz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possible differences between physiological and psychological preparedness to increase training workload reinforce the importance of qualitative or quantitative psychological assessment throughout training, and further studies are needed to elucidate these aspects. In addition, it should be noted that SIT-WB participants had a certain level of autonomy over their training intensity, which may have also been important in satisfying basic psychological needs promoting autonomous motivation and enjoyment (Rodrigues et al, 2020). Improved fitness through training may also have served to build up competence and help maintain enjoyment over time (Heisz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies that investigated perceived enjoyment, however, assessed only acute responses to a single bout and, therefore, these might not reflect the overall enjoyment of a longer-term training program. Rodrigues et al (2020) observed that exercise enjoyment had the strongest effect on persistence to exercise over a 6-month period in gym exercisers and, accordingly, suggested that enjoyment is important for maintaining exercise participation. Presently, however, it is not clear whether the same association is upheld in interval training interventions, not even in healthy adult individuals.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, future studies should assess the possibility of specific paths between need-supportive and need-thwarting behaviors on BPN satisfaction and also needs frustration on cognitive and behavioral outcomes. Recent studies [49] have shown that motivational sequences co-occur, displaying significant differences among a bright and a dark side of motivation. Given the ongoing importance of understanding the predictability of grit in cognitive and behavioral outcomes, this study opens doors to new research questions on how grit experimentally manipulated could account for changes in college grades.…”
Section: Limitationsmentioning
confidence: 99%
“…In contrast, external motivation is a state in which individuals' behavior is controlled by specific external factors [36]. Several studies indicate that individuals who exhibited self-determined types of regulation show more persistence in PA engagement [37], exercise adherence [38], PA intentions [39], and enjoyment of physical exercise [40]. Participants in the current study reported that wearing the Fitbit and playing exergames were enjoyable experiences and expressed their wishes to continue the exercise programs.…”
Section: Discussionmentioning
confidence: 68%